2013
DOI: 10.9775/kvfd.2012.7902
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Treatment with Chitosan on Sensory and Chemical Quality Parameters of Frozen Shrimp

Abstract: ÖzetBu çalışma dondurulmuş karideslerde kalitenin uzun süre korunabilmesi için kitosanla muamele edilmesinin etkisini araştırmak için yapılmıştır. Denemeler Marmara Denizinden avlanan derin su pembe karidesi (Parapenaeus longirostris) üzerinde gerçekleştirilmiştir. Taze karidesler sekiz gruba ayrıldıktan sonra çeşme suyu (kontrol) ile sodium metabisülfit (2500 mg/L), 4-heksilresonsinol (50 mg/L), kitosan (5 g/L), sitrik asit (50 mg/L) ve biberiye ekstraktı (50 mg/L) kombinasyonlarını içeren solüsyonlarda 10 dk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…In general, it was observed that both high and low deacetylation degrees of chitosan are effective in delaying the formation of melanosis. Similar to the findings presented here, Bingöl et al 57 found in their study on the quality of frozen shrimps treated with chitosan that samples from all groups were consumable, even at the end of the storage period, according to the panelist evaluations. However, they reported that the control group samples received lower taste and odor scores than the treatment groups.…”
Section: Discussionsupporting
confidence: 89%
“…In general, it was observed that both high and low deacetylation degrees of chitosan are effective in delaying the formation of melanosis. Similar to the findings presented here, Bingöl et al 57 found in their study on the quality of frozen shrimps treated with chitosan that samples from all groups were consumable, even at the end of the storage period, according to the panelist evaluations. However, they reported that the control group samples received lower taste and odor scores than the treatment groups.…”
Section: Discussionsupporting
confidence: 89%
“…When the shelf life of the food is increased, the producer is provided with a longer time to market the product and the consumer to consume it and the product becomes more economical (Morrais and Kai 1981;Mermelstein, 1998). Cold marinated (Cadun et al, 2005;Kalıştır, 2008;Cadun et al, 2008), baked and marinated (Bilgin et al, 2006;Erdem and Bilgin, 2004) and freeze (Bingöl et al, 2013) of different shrimp species; are found in the literature. Although there is some seafood (Dalgıç, 2000;Ozogul et al, 2010;Balıkçı, 2009, Karslı, 2013Keskin, 2019) where both smoking and marination are applied together, no such study has been observed in shrimp.…”
Section: Introductionmentioning
confidence: 99%